Strategi Berinvestasi terhadap Keberhasilan Investasi Saham Syariah di Pasar Modal Syariah - Widia Roker; Ibnu Waseu (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Stocks and the Indonesian capital market coexisted in Indonesia in 1912, when the Indonesian capital market was first established. An Islamic regulation master named Abdurrahman Isa contends that stock trading exchanges are permitted in religion, including shares gave by banking organizations, where a portion of the exercises are revenue based credit. This is based on the circumstances of Muslims, who, in his opinion, are in a dhorurat state. This study made use of literature research, which uses information from books and other sources to investigate the method for putting into practice investment in sharia stocks as a tool for economic improvement. The English word investment, which means to plant, was adopted from the British language. According to the Dictionary of Capital Market and Financial Terms, "investment" refers to putting money or capital into a business with the intention of earning a profit. The Capital Market Law regulates the sharia capital market, which is a capital market that does not violate sharia law. In this instance, the Capital Market and Financial Institutions Supervisory Agency (Bapepam-LK) continues to oversee the sharia capital market. The fundamental difference between the sharia capital market and the conventional capital market is that the sharia capital market must adhere to sharia law in all transaction mechanisms and issuers traded in it. In other words, there is no significant difference between the two markets.